Incentive-based, instructed, and social observational extinction of avoidance: Fear-opposite actions and their influence on fear extinction. (February 2021) - Pittig, Andre; Wong, Alex H.K.
Abstract: Avoidance is a transdiagnostic symptom of clinical anxiety and its reduction a major focus of cognitive-behavioral treatments. This study examined the instrumental extinction of goal-directed avoidance by means of incentives, verbal instruction, and social observation and their influence on fear extinction. Participants acquired conditioned fear and instrumental avoidance responses (N = 160). In four randomized groups, the reduction of avoidance by incentives for non-avoidance, instructions to refrain from avoidance, and social observation of non-avoidance was compared to no intervention before removing the aversive outcome. Conditioned fear when avoidance became unavailable subsequently was tested. Incentives, instruction, and observation all reduced avoidance better than no intervention, however, with different degrees and influence on conditioned fear. Incentives and instructions strongly reduced avoidance despite high levels of fear (i.e., fear-opposite actions). This initiated fear extinction, thereby reducing conditioned fear when avoidance became unavailable. Social observation directly reduced conditioned fear, presumably because it conveyed additional information about the absence of the aversive outcome. However, observation only moderately reduced avoidance and resulted in higher fear when avoidance became unavailable. The effects of social observation may depend on the nuances of the demonstrator's behavior. The clear effects of incentive and instructions provide support for clinical interventions to reduce avoidance during exposure therapy and can serve as experimental models for their controlled investigation. Highlights: Incentives, instruction, & observation better reduce avoidance than no intervention. Incentives & instructions strongly reduce avoidance despite high fear. These fear-opposite actions initiated fear extinction, reducing return of fear. Social observation directly reduced conditioned fear due to additional information. Observation only moderately reduce avoidance and resulted in more return of fear.